EPDR1 levels and tumor budding predict and affect the prognosis of bladder carcinoma - Yang, Yue; Xu, Hong; Zhu, Han; Yuan, Dan; Zhang, Hanchao; Liu, Zhengdao; Zhao, Faliang; Liang, Guobiao (Frontiers in Oncology, 2022)
Background: Bladder carcinoma is a common malignancy of the urinary system. The previous study showed that EPDR1 expression was significantly related to the carcinogenesis and progression of bladder carcinoma Methods: We retrospectively reviewed the records of 621 patients who were newly diagnosed with bladder carcinoma between January 2018 and August 2020 at The Affiliated Hospital of Zunyi Medical University. We conducted immunohistochemistry of EPDR1 in tumor tissues. Meanwhile, tumor budding evaluation was also carried out by 2 independent experienced pathologists. Results: 80 patients were included in this study with a median age of 66 years (range; 42–88 years). 45% of the patients (36/80) were non-muscle-invasive bladder carcinoma patients, while 55% of muscle-invasive bladder carcinoma(44/80). The follow-up time was from 6 months to 36 months. We found that there were significant differences in expression of EPDR1 in the tumour pT stages(p<0.05), pM stages(p<0.05), and pN stages(p<0.05). Meawhile, a higher expression of EPDR1 indicated a poor outcome for the patient(p<0.05). A tendency toward a worse status of the patient was accompanied by a high positive rate (p<0.001). Moreover, the IOD of EPDR1 had a positive relationship with TB (p<0.05).. Furthermore, we found that EPDR1 and tumour budding could be crucial factors for affecting the prognosis of bladder carcinoma, even better than pTMN(Riskscore=(0.724)* pT_stage +(4.960) *EPDR1+(4.312)*TB). Conclusion: In conclusion, bladder cancer patients with high expression levels of EPDR1 had poor survival outcomes. The combination of TB and EPDR1 levels could predict the prognosis for muscle-invasive bladder cancer patients.